Decolonising AI: A critical approach to education and social justice - Dean Collin Langeveldt; Doniwen Pietersen (Interdisciplinary Journal of Education Research, 2024)
Artificial intelligence (AI) technologies present significant opportunities for education, enabling personalised learning, data-driven decision-making, and innovative pedagogy, particularly in higher education environments. However, such technologies also pose ethical, cultural, and political challenges. Many scholars have not adequately considered social justice and inclusivity, which could highlight inequalities in higher education. A critical examination of AI’s use in teaching and learning spaces is therefore crucial to ensure that its implementation serves the common good and upholds human rights. This conceptual article foregrounds a decolonial and inclusive approach to the use of AI, exploring the techniques, outcomes, and obstacles faced by practitioners applying AI in their teaching, learning, and research practices. Drawing on theoretical frameworks such as the decolonised perspective, which aligns with and is supported by technological pedagogical content knowledge, facilitated the research underpinning this article. The results reveal the need for cultural responsiveness, ethical awareness, and critical engagement among stakeholders while addressing structural and systemic barriers to achieving social justice and equity in AI education. The article contributes to the literature on decolonising AI and levelling the proverbial 'playing field' in education. It advocates for sensitivity to culturally appropriate curricula in higher education to foster collaborative learning environments, ensure accountability, and promote diversity and inclusion among educators and learners.